A Rare Case of Chronic Intracerebral Foreign Body - Imran, Naufal Hilmy; Wahyudi (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Introduction: Intracranial foreign bodies are usually caused by trauma that penetrates the cranium. Gunshot wounds are the most common cause, while non-missile intracranial penetration is rare. The patient’s clinical condition highly depends on the mechanism, anatomical location of the lesion, and related injuries. Possible complications include intracerebral hemorrhage, contusion, major injury on the vascular, and meningitis. In this article, we report case of intracerebral nail extraction from a patient with right cerebral foreign body. Case presentation: A 22-year-old man with a history of unspecified schizophrenia reported with reduced awareness accompanied by weakness of his left limb. During a head CT scan of the head, there are several tubular foreign bodies in the right cerebral. Craniotomy for foreign body extraction and drainage of the cerebral abscess is immediately performed. Four days after surgery, the patient had increased awareness, although there was no significant improvement in motor strength. One month after discharged from hospital there was slight improvement in motor strength. Conclusion: Extraction of foreign bodies by a surgical procedure is mandatory and should be performed thoroughly. The administration of antibiotics, anticonvulsants, physiotherapy, and psychiatric follow-up should be added to the treatment of this patient.